Case study: Leona Handmade: transforming a local label into a luxury brand - Grossi, Alice Simões (2023)
Leona Feito à Mão, founded by Alice Grossi in December 2020, translates heritage with its family history and the crochet craftsmanship passed down through generations. The brand's mission is to empower women artisans in southeast Brazil, particularly those who live in the rural areas in Minas Gerais. The company began creating affordable crochet clothing products with meaningful stories promoted on social media and its website. The brand cultivated a loyal customer base and achieved substantial growth during the first year of operations. However, the consumer shifting preferences prompted Leona to pivot the business towards the luxury market with the launch of the Catharina Bag, increasing the conversion rates. In the current scenario, the founder faces a strategic decision: continue entering the luxury market or explore alternative directions to maintain the business.